Nilai - Nilai Qurani dan Sunnah Nabi dalam Praktik Jual Beli Pada Pasar Terapung di Kalimantan Selatan - Ariyadi Ariyadi (Anterior Jurnal, 2018)
This research departs from the activities that are often done by the Banjar community which is always identified with Islam. Sociologically, the identity of the Banjar community with Islam refers to a social identity that reflects a common social bonding foundation. Historically, Islam was used as a pivot of trading system by Banjar society. This means that the behavior of Banjar people can be searched the source on Islamic references, including in it is the behavior of Banjar people in trading and selling both in the study of verses and hadith. This study aims to find out how to buy and sell floating market in South Kalimantan, how to buy and sell transaction agreement in floating market in South Kalimantan and what is the underlying proposition of people in South Kalimantan in trading and selling floating market. Thus, at least that has been the point of trouble can be revealed and can be scientific information that brightens. This research is a field research (field research), this research is descriptive, where the data collected were analyzed qualitatively. To obtain the required data. The author conducted observations, documentation, and interviews directly with some traders Floating Market in South Kalimantan. Through qualitative analysis technique from this research resulted from the findings: First, how to buy and sell floating market in South Kalimantan (1) Barter, (Goods with equivalent goods) (2) Sale and purchase transaction of goods by means of exchange (money).